Stitching competition with digital threads: Unveiling the drivers of competitive success in the apparel sector - Emmanuel Susitha; Amila Jayarathne; H. M. R. P. Herath (PLoS ONE, 2025)
This study explores and validates the dimensions of digital capabilities and competitive performance within the apparel industry, aiming to develop a robust, multidimensional measurement instrument. Employing a sequential QUAL→QUAN exploratory design, the research began with in-depth interviews with key industry experts to identify critical constructs. These insights informed the subsequent quantitative phase, in which exploratory factor analysis and confirmatory factor analysis were applied to confirm the factor structure and validate the instrument. The study identifies four key dimensions of competitive performance in the apparel supply chain: customer satisfaction, better utilisation of resources, collaboration to compete, and strategic advantage. Process and technical digitalisation emerged as essential components of digital capabilities, reflecting the dual role of digital infrastructure and operational integration in enhancing performance. Theoretically, this research contributes by introducing validated instruments grounded in the Resource-based view, the Dynamic capabilities view, and the Extended resource-based view, offering an empirical framework that links digital capabilities with competitive performance. Practically, the instrument provides apparel manufacturers with a diagnostic tool to assess digital maturity and strategically align digital initiatives with performance goals. These findings are particularly relevant for firms navigating rapid technological change and seeking sustained global apparel supply chain competitiveness.